Motor competence of 10 years old children with different athletics practice years - Nataniel Lopes; Rui Matos; Nuno Amaro; Luís Coelho; Raúl Antunes; Miguel Jacinto; Filipe Rodrigues; Diogo Monteiro; Sergio Ibáñez (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The present study aimed to verify whether, in children of 10 years of age practicing athletics, a greater number of years of practice of this modality would correspond to higher values of motor competence (MC), as determined by the Motor Quotient (MQ) in the Körperkoordinationstest Für Kinder (KTK). The cross-sectional and descriptive study was conducted in an athletics club in Portugal. Thirty-two children were evaluated, 15 female (10.4±0.25 years of age, 2.5±0.92 years of practice) and 17 male (10.4±0.22 years of age, 2.2±1.1 years of practice). Although no significant differences were found between children with one or two years of athletics practice and children with three or four, a moderate positive correlation was found between the time of practice (TP) and MC in girls (ρ=0.543, p=0.036). Mean MC results were considerably higher (both sexes) than the generality of studies often reveal. Finally, there were no significant differences on MC of boys and girls. The present results allow us to speculate that athletics may have helped to fill some gaps in motor coordination so often observed in girls, and the time of practice may have been especially beneficial for this group. It is suggested a longitudinal study to, more than confirm the detected association, verify what happens with boys’ and girls’ MC throughout the years of athletics practice.